2013
DOI: 10.1097/pcc.0b013e31827212c0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Decreases Cerebrospinal Fluid Asymmetric Dimethylarginine Levels in Children With Traumatic Brain Injury

Abstract: Objectives Pathological increases in asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase (NOS) inhibitor, have been implicated in endothelial dysfunction and vascular diseases. Reduced NO early after traumatic brain injury (TBI) may contribute to hypoperfusion. Currently, methods to quantify ADMA in the cerebrospinal fluid (CSF) have not been fully explored. We aimed to develop and validate a method to determine ADMA in the CSF of a pediatric TBI population and to use this method to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Similarly increased ADMA levels accompanied by decreased NO levels in CSF and NOS inhibition have been demonstrated in cases of brain injury caused by aneurysmal subarachnoid hemorrhage [ 27 , 28 ]. Furthermore, Thampatty et al reported elevated CSF ADMA level within 3 days after TBI in children [ 29 ]. The delayed detection of elevated ADMA levels in CSF and serum parallels the timescale for apoptosis and neuronal cell-death as well as the time-course of blood brain-barrier breakdown after TBI [ 17 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly increased ADMA levels accompanied by decreased NO levels in CSF and NOS inhibition have been demonstrated in cases of brain injury caused by aneurysmal subarachnoid hemorrhage [ 27 , 28 ]. Furthermore, Thampatty et al reported elevated CSF ADMA level within 3 days after TBI in children [ 29 ]. The delayed detection of elevated ADMA levels in CSF and serum parallels the timescale for apoptosis and neuronal cell-death as well as the time-course of blood brain-barrier breakdown after TBI [ 17 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent work found that children treated with hypothermia after TBI had reduced CSF levels of dimethylarginine. 8 Dimethylarginine is a nitric oxide synthase inhibitor, blocking production of the potent vasodilator nitric oxide. Thus, hypothermia acutely permits vasodilation and increased perfusion to cerebral tissues which may mitigate secondary damage of TBI.…”
Section: Immediate Hypothermia Treatmentmentioning
confidence: 99%